1988
DOI: 10.1002/maco.19880391102
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical impedance spectroscopy as a monitoring tool for passivation and localized Corrosion of aluminum alloys

Abstract: Dedicated to Professor Dr. Helmut Kaesche on the occasion of his 60th birthdayPitting and crevice corrosion of A1 alloys and Al-based metal matrix composites can be detected by characteristic changes of the impedance spectra in the low frequency region. A pitting model has been developed which is in agreement with the experimental data. A fitting procedure has been used to analyze a large number of data which have been obtained for as-received samples and samples which had been passivated in CeCI3 solutions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…However, the decrease in the size of the semicircle for mc-Al compared to pc-Al indicates that mc-Al is more susceptible to corrosion in the acidic environment. The Nquist plots are characterized by three time constants consisting a large capacitive loop at high frequencies (HF), an inductive loop at medium frequencies (MF) followed by the second capacitive loop at low [15,17,18] since the oxide film is considered to be a parallel circuit of a resistor due to the ionic conduction of the oxide film and a capacitor due to its dielectric properties [18]. Another possible explanation for the origin of the capacitive loop at high frequency as put forward by Brett [19] and reported in [20] is the reactions involved in the formation of the oxide layer.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…However, the decrease in the size of the semicircle for mc-Al compared to pc-Al indicates that mc-Al is more susceptible to corrosion in the acidic environment. The Nquist plots are characterized by three time constants consisting a large capacitive loop at high frequencies (HF), an inductive loop at medium frequencies (MF) followed by the second capacitive loop at low [15,17,18] since the oxide film is considered to be a parallel circuit of a resistor due to the ionic conduction of the oxide film and a capacitor due to its dielectric properties [18]. Another possible explanation for the origin of the capacitive loop at high frequency as put forward by Brett [19] and reported in [20] is the reactions involved in the formation of the oxide layer.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…1a). The capacitive loop (at high frequencies) could be assigned to the relaxation process in the natural oxide presents on the surface of the aluminum sample and its dielectric properties 17,19 . Namely, the oxide film is considered to be a parallel circuit of a resistor due to the ionic conduction in the oxide film, and a capacitor due to its dielectric properties.…”
Section: Methodsmentioning
confidence: 99%
“…e-mail: f-baghaei@mail.uk.ac.ir The inductive loop (at low frequencies) could be attributed to the relaxation process in oxide presents on the electrode surface and it is obtained by adsorption species as ( ads and 19 . These data are consistent with mechanism that proposed the adsorption of SO 4 2-ions on to the oxide surface forming oxide-sulfate aluminum in acidic solutions.…”
Section: Ac Impedancementioning
confidence: 99%
“…Deviation of this kind is referred to as frequency dispersion, and has been attributed to inhomogeneities of the solid surfaces. 56 Mansfeld et al 47,48 have suggested an exponent n in the impedance function as a deviation parameter from the ideal behavior. By this suggestion, the capacitor in the equivalent circuit can be replaced by the so-called constant phase element (CPE), which is a frequencydependent element and related to surface roughness.…”
Section: Electrochemical Impedance Spectroscopy (Eis) Studiesmentioning
confidence: 98%
“…47,48 The oxide film is considered to be a parallel circuit of a resistor due to the ionic conduction in the oxide film and a capacitor due to its dielectric properties. The capacitive loop is corresponding to the interfacial reactions, particularly, the reaction of aluminum oxidation at the metal/oxide/electrolyte interface.…”
Section: Electrochemical Impedance Spectroscopy (Eis) Studiesmentioning
confidence: 99%